'It's From My Grandma.' How Jewellery Becomes Singular. (2nd January 2017) - Ahde-Deal, Petra; Paavilainen, Heidi; Koskinen, Ilpo
Abstract: Most objects in our lives are barely noticed and not much more than consumer goods. Some objects, however, become so important to people that they start to shape their understanding of their self. This paper looks at how some pieces of jewellery become parts of what we call the core self. The study collected stories about jewellery in Helsinki and Chicago between 2008 and 2010. The key process that transforms some pieces of jewellery to constituent parts of the self is family history and connections that some pieces create between generations of women. We close the paper by arguing that design researchers need to pay more attention to social processes that turn some objects into heirlooms, rather than focus on consumption only.